Effect of Mg doping on optical properties of ZnO films by ultrasonic spray pyrolysis - Sutatip Thonglem (2018)
Effect of Mg doping on optical properties of ZnO films was investigated in this work. The films were prepared by ultrasonic spray pyrolysis on glass substrates heated at 350-450°C in air. The atomic percentage ratios of Mg/Zn were 0-9 at.%. All films were ZnO polycrystalline structure with preferred orientation (002) plane. A shift of the absorption edge in transmittance spectra of films occurred with added Mg content and shifted to a lower wavelength with increased Mg content. This shift behavior was influenced by the band gap of doped ZnO films, the band gap increasing with Mg content. © 2014 Taylor & Francis Group, LLC.